NEED ANALYSIS STAGE IN RECONSTRUCTING SYLLABUS AND DEVELOPING TEACHING MATERIALS FOR ORACY IN ACADEMIC CONTEXT SUBJECT - Wulandari, Bunga Ayu; Hustarna, Hustarna (International Journal of Language Education, 2020)
The focus of this current article is on the needs analysis phase in a project exploring the reconstruction of a syllabus and developing teaching materials for Oracy in Academic Context subject. The subject has only been recently incorporated in the curriculum of the English Department in Teacher Training and Education Faculty (FKIP), at Universitas Jambi in Indonesia. Therefore, the syllabus has not fully reviewed since it was created. This current paper describes the need analysis stage as one of the research and development (R & D) phases which consists of analysis, design, development, and evaluation (ADDIE) model in developing the syllabus for this subject. Adapting Nation and Macalister?s framework (2010), this stage considers the lecturers?, the head of the English department?s, and the students? point of views. The data from the needs analysis phase point to the importance of this stage in redesigning the syllabus and developing teaching materials. Using the data from the all four sources, the researchers in this current research, as syllabus and materials developers can begin to identify the most important aspects to be included in the syllabus and the materials to be included.